Generation of hiPSCs with ABO c.767T>C substitution: resulting in splicing variants - Jin, Yinge; Chen, Tao; Zheng, Wei; Xi, Jiahui; Zi, Yin; Wang, Jinling; Chi, Yue; Chen, Min; Zou, Qingjian; Tang, Chengcheng; Lai, Liangxue; Zhou, Xiaoqing (Frontiers in Genetics, 2023)
ABO blood group system has important clinical significance in the safety of blood transfusion and organ transplantation. Numerous ABO variations especially variations in the splice sites have been identified to be associated with some ABO subtypes. Here, we performed the c.767 T>C substitution of ABO gene in human induced pluripotent stem cells (hiPSCs) by adenosine base editor (ABE) system and described its characteristics at genome level in detail. The hiPS cell line with c.767 T>C substitution maintained a normal karyotype (46, XX), expressed pluripotency markers, and showed the capability to spontaneously differentiate into all three germ layers in vivo. The genome-wide analysis demonstrated that the c.767 T>C substitution in ABO gene did not cause any detected negative affect in hiPSCs at genome level. Splicing transcript analysis revealed that splicing variants were observed in the hiPSCs with ABO c.767 T>C substitution, which probably make a significant effect on the formation of the rare ABO*Ael05/B101 subtype.